ChemInform Abstract: Enantioselective Gold Catalyzed Dearomative [2 + 2]‐Cycloaddition Between Indoles and Allenamides. Issue 26 (June 2015) - Jia, Minqiang; Monari, Magda; Yang, Qing‐Qing; Bandini, Marco
Abstract The [2+2]‐cycloaddition between indoles and allenamide gives access to methylenecyclobutanes representing competent buildings block in organic synthesis which are especially attractive in future synthesis of indole based alkaloids.